Analysis of Effectiveness and Efficiency in Measurement of DKI JAKARTA's Financial Performance in 2019-2020: Analisis Efektivitas dan Efisiensi dalam Pengukuran Kinerja Keuangan DKI JAKARTA Tahun 2019-2020 - Febriyanti, Arinda Nur Alifah; Nurasik, Nurasik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effectiveness and efficiency in measuring DKI Jakarta's financial performance in 2019-2020, whether DKI Jakarta programs in 2019-2020 have been effective and efficient for the community and become an internal evaluation for DKI Jakarta in 2019-2020. This research method uses quantitative descriptive, data collection is carried out with work programs on the 2019-2020 financial performance report of DKI Jakarta. In measuring the effectiveness of the 2019-2020 DKI Jakarta work progra,. The results showed that (1) The research analysis on measuring the effectiveness of the DKI Jakarta government's performance in 2019-2020 was included in the effective category. Of all program realizations, the program plans are categorized as effective on average. This shows that the output programs that have been made by the DKI Jakarta government in 2019-2020 have reached the community according to their potential. (2) Research analysis on measuring the efficiency of the DKI Jakarta government's performance in 2019-2020 is in the efficient category. Of all budget realizations from the budget plan, it is in the average category, although in detail there are several programs that are not available due to the COVID-19 pandemic.